The mating game - Ferguson, Lana (Berkley Romance, 2025)
After experiencing unexpected physical changes, contractor Tess Covington learns she is a late-presenting omega wolf shifter. Determined to complete a renovation project despite the upheaval, she attempts to avoid contact with alpha shifters as advised. Hunter Barrett, an alpha managing a struggling lodge, reluctantly hires Tess for the job even as both try to maintain distance. As they work together, their mutual attraction complicates their plans and challenges their personal boundaries.